Effect Of Mangrove Leaf Extract Dosage Rhizophora Mucronata Lmk. On The Viability Of Hela Cells - Rohadatul Alsy (Journal of Stem Cell Research and Tissue Engineering, 2021)
This study aims to determine the IC50 value of the mangrove leaf extract type Rhizophora mucronata Lmk. against the viability of Hela cells. The samples extracted with three types of solvents were previously conducted preliminary research on phytochemical compounds and their toxicity values with the Meted Brine Shrimp Letality Test (BSLT). In the toxicity test, the highest level of toxicity was obtained in the ethanol extract with a value of 166.72± 7.72 ppm, then the sample was continued for the cytotoxicity test using the MTT method. The dosage variants used in this study were 62.5 ppm; 125 ppm; 250 ppm; 500 ppm; and 1000 ppm. The variation in dosage shows an effect on the viability of Hela cells, namely a decrease in the percentage of living cells along with the addition of the ethanol extract dose of Rhizophora mucronata Lmk leaves. which is given. And the IC50 value obtained from this study was 63.67 µg / mL with the toxic category